The Urgency of Strengthening DPD RI In Regional Lawmaking Amid Central-Regional Polarization In Asymmetric Decentralization - Sholihin Bone; Rahayu; Ratna Herawati; Agnes Fitryantica; Juniardi Windraswara (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
The Regional Representative Council of the Republic of Indonesia (DPD RI) was constitutionally established as a representative body for the regions within the national political system. However, its role in the legislative process remains weak and limited. This limitation becomes increasingly problematic amidst the growing polarization between central and regional governments, as well as regulatory conflicts caused by imbalances in legislative authority over laws that directly impact the regions. Furthermore, the challenges of regional development in an era of asymmetric decentralization demand a stronger and more active role from the DPD RI to ensure that national policies align with local needs. This study aims to evaluate the legislative role of the DPD RI and to propose a model for strengthening its authority in a more effective and structural manner. The research employs a normative juridical method with a comparative approach, supported by theoretical frameworks and global practices in bicameral legislative systems. The key finding of this research is a conceptual proposal and normative design of a